Stock price crash risk in emerging markets: the role of corporate governance and price informativeness / Ling Zhang ... [et al.] - Ling, Zhang; Rasheed, Muhammad Shahid; Kouser, Shahzad; Mohd Nordin, Nordina (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
This study examined the role of stock price informativeness and corporate governance in mitigating stock price crash risk. Despite the critical importance of information in financial markets, most prior studies have relied on traditional measures of informativeness, such as stock price synchronicity, which failed to account for the complexities of return distributions with fat tails. To address this limitation, this study introduced a novel copula-based measure of stock price informativeness that captured the nonnormal distribution of stock returns. The findings indicated that higher stock price informativeness reduced stock price crash risk in Pakistani firms. Additionally, the study revealed that large and independent boards were ineffective in enhancing the information environment in family-dominated firms, where information concealment contributed to increased crash risk. Moreover, institutional ownership was positively associated with crash risk, highlighting the passive role of institutional investors. These findings suggested that regulators in emerging markets, such as Pakistan, should prioritize ownership regulations over traditional boardroom governance to reduce information asymmetry and mitigate crash risk.